Experimental characterization of composite laminates under low-velocity multi-impact loading. (July 2019) - Ezéckiel Amouzou, Adadé Seyth; Sicot, Olivier; Chettah, Ameur; Aivazzadeh, Shahram
The use of composite materials undergoes a significant growth in many industries including aeronautic, railway, and automotive. Laminated composites are often subjected to severe loading conditions such as hailstones on aircraft and road gravels on automobiles. The present paper deals with the damage tolerance in carbon fiber-reinforced polymer structures caused by low velocity multiple impacts. Low velocity multi-impact tests at different energy levels (10, 15, and 20 J) are performed in order to simulate the gravels' impact conditions corresponding to mass of 10–50 g for velocity of 100–150 km/h. These tests were carried out on composite laminates with three types of stacking sequences (AERO, QIQH45, and QIQH60). AERO, widely used in aviation industry, is symmetric stacking sequence, and the two others QIQH45 and QIQH60 are quasi-isotropic and quasi-homogeneous laminates based on 45° and 60° ply orientation, respectively. Two specific parameters D and d are deduced from force–displacement and force–time responses which make it possible to rank the three stacking sequences to their damage tolerances. The impact damage assessment within the composite material with non-destructive testing method using ultrasonic inspection gives a good correlation with parameter D . Better impact damage tolerance is achieved with QIQH45 than the QIQH60 and AERO laminates. The parameter D can be regarded as a failure criterion for dimensioning of composite structures subjected to repetitive impacts.